Renal genetics in Australia: Kidney medicine in the genomic age. Issue 3 (18th October 2018) - Jayasinghe, Kushani; Quinlan, Catherine; Stark, Zornitza; Patel, Chirag; Mallawaarachchi, Amali; Wardrop, Louise; Kerr, Peter G; Trnka, Peter; Mallett, Andrew J; ,
ABSTRACT: There have been few new therapies for patients with chronic kidney disease in the last decade. However, the management of patients affected by genetic kidney disease is rapidly evolving. Inherited or genetic kidney disease affects around 10% of adults with end‐stage kidney disease and up to 70% of children with early onset kidney disease. Advances in next‐generation sequencing have enabled rapid and cost‐effective sequencing of large amounts of DNA. Next‐generation sequencing‐based diagnostic tests now enable identification of a monogenic cause in around 20% of patients with early‐onset chronic kidney disease. A definitive diagnosis through genomic testing may negate the need for prolonged diagnostic investigations and surveillance, facilitate reproductive planning and provide accurate counselling for at‐risk relatives. Genomics has allowed the better understanding of disease pathogenesis, providing prognostic information and facilitating development of targeted treatments for patients with inherited or genetic kidney disease. Although genomic testing is becoming more readily available, there are many challenges to implementation in clinical practice. Multidisciplinary renal genetics clinics serve as a model of how some of these challenges may be overcome. Such clinics are already well established in most parts of Australia, with more to follow in future. With the rapid pace of new technology and gene discovery, collaboration between expert clinicians, laboratory and research scientists is of increasing importance to maximize benefits to patients and health‐care systems. Summary at a Glance: The authors reckoned the importance of genomic testing as it allows better understanding of disease pathogenesis, provides prognostic information and facilitates development of targeted treatment, particularly for patients with inherited or genetic kidney disease.